Legal Responsibilities of Parties Involved in Breaking BRI Accounts Through the WhatsApp Application in the Legal Perspective of Engagement - Imelda Martinelli; Pascal Amadeo Yapputro; Eriyan Rahmadani Dianova (Pelopor Publikasi Akademika, 2023)
Advances in banking technology are developments in information technology that have had a significant impact on the banking industry. Technological developments have helped banks to improve the efficiency of services and products offered to customers. One of the products of technological advances in banking is Mobile Banking, where customers can make transactions anywhere and anytime. However, this has become a new challenge in the law of engagement related to transactions made by individuals with each other online. This research aims to find out the relationship between account breach through the application with the law of engagement, as well as the responsibility of the parties involved. This research uses normative juridical research method. The conclusion of this research is that there is no banking law on Mobile Banking, the customer is responsible for the imprudence committed against his bank account